NAUBAT TRADITION IN GREAT SELJUKS - Timur VURAL (Fırat University, 2019)
The tradition of military music, which has been living in every period of Turkish history, appeared as tradition of naubat (tablhane) in Great Seljuks. The naubat band which is a sign of domination of the Great Seljuks, took part in many environment from the palaces to the fields of battle. The Great Seljuks, as a Muslim-Turkish state, mixed tradition of naubat, which its roots based on pre-Islamic period, and Islamic culture. In this study of descriptive research, based on literature, it is investigated that the tradition of naubat in Great Seljuks State, its general features, historical process and its meaning.